Modified bentonite, preparation method and application in preparing cosmetic blush cream

By inorganic and organic modification of bentonite, modified bentonite was prepared, which solved the problem of insufficient performance of bentonite in daily chemical products, achieved significantly improved dispersion, thickening performance, water absorption and expansion performance, and had excellent breathability and light stability.

CN118978166BActive Publication Date: 2025-03-25저장 아얀 바이오텍 컴퍼니 리미티드
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411467132.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-21
Publication Date
2025-03-25
Estimated Expiration
2044-10-21

AI Technical Summary

Technical Problem

There are problems with insufficient performance in the application of existing bentonite in daily chemical products, especially in terms of water absorption, thickening and light stability.

Method used

Modified bentonite is prepared by inorganic and organic modification of bentonite, including ball milling with lithiated montmorillonite and specific organic compounds. This modified bentonite is used in both aqueous and oily components.

Benefits of technology

Modified bentonite significantly improves dispersion, thickening properties and water absorption and expansion properties, and also has excellent breathability, stable physical properties and good light stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118978166B_ABST
    Figure CN118978166B_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of bentonite, and in particular to modified bentonite, a preparation method and an application thereof in preparing a makeup blush cream. The present invention purifies Liaoning bentonite and then treats it with lithium carbonate and oxalic acid to obtain lithiated montmorillonite, and then mixes the lithiated montmorillonite with 3-(4-ureaamino)propyltriethoxysilane and N,N'-dimethylthiourea to obtain modified bentonite by ball milling. The dispersibility, thickening performance and water absorption and swelling performance of the modified bentonite are significantly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of bentonite, and in particular to modified bentonite, a preparation method and application in preparing cosmetic blush cream. Background Art

[0002] Bentonite is a layered aluminosilicate mineral, the main component of which is montmorillonite. The crystal structure of montmorillonite is composed of two layers of silicon-oxygen tetrahedron [Si-O4] with a layer of aluminum-oxygen octahedron [AlO2-(OH)4] in the middle, which is a typical 2:1 monoclinic structure. Montmorillonite is a layered clay that is continuously stacked with such a 2:1 monoclinic structure. There are certain gaps between adjacent orthorhombic layers, and the gaps are filled with a large number of anions and cations that can be used for exchange, such as calcium ions, magnesium ions, aluminum ions, iron ions, sodium ions and chloride ions. The cations in the interlayer gaps of montmorillonite are easily exchanged and have a large ion exchange capacity. In reality, bentonite is often divided into hydrogen-based bentonite, calcium-based bentonite, sodium-based bentonite, magnesium-based bentonite, etc. according to the type of cations in the interlayer gaps. Bentonite is widely used in environmental protection, chemical industry, nuclear industry, medicine, petroleum, papermaking and other fields because of its large surface area, good adsorption performance, heat resistance and expansion performance. It has the reputation of "universal clay" and has broad market development prospects.

[0003] Bentonite mainly exhibits many excellent physical and chemical properties in daily chemical products, such as water absorption and hydrophilicity, thixotropy, adsorption, dispersibility, plasticity, suspension, colloid, lubricity and non-toxicity. However, in order to adapt to the application of various daily chemical products, it needs to be modified. Summary of the invention

[0004] In view of this, the present invention provides a modified bentonite, a preparation method and an application in the preparation of a cosmetic blush cream, so as to improve various properties of the bentonite and apply it to cosmetics.

[0005] One of the purposes of the present invention is to provide a method for preparing modified bentonite, comprising:

[0006] (1) The crushed Liaoning bentonite ore particles are mixed with an aqueous solution containing sodium silicate and sodium hexametaphosphate to prepare a slurry, and the slurry is ground to obtain a dispersed bentonite slurry.

[0007] (2) The bentonite slurry obtained in step (1) is diluted and centrifuged to obtain the concentrate slurry on the upper layer.

[0008] (3) Acid is added to the concentrate slurry obtained in step (2) to adjust the pH to 4.0-5.0, and then centrifuged to obtain the concentrate, which is then washed with water.

[0009] (4) The washed slurry is centrifuged, the paste layer is removed and dried to obtain the concentrate.

[0010] (5) The dried sample obtained in step (4) is crushed and sieved to obtain purified montmorillonite.

[0011] (6) Purifying montmorillonite slurry with water, mixing with lithium carbonate and oxalic acid, high-pressure homogenization, standing for aging, drying, and sieving to obtain lithiated montmorillonite.

[0012] (7) The lithiated montmorillonite is mixed with 3-(4-ureaamino)propyltriethoxysilane and N,N'-dimethylthiourea, and then dried and ball-milled to obtain the modified bentonite.

[0013] Specifically, the particle size of the Liaoning bentonite ore particles in step (1) is less than 1 cm, the amount of sodium silicate added is 2.5% by weight of the bentonite, the amount of sodium hexametaphosphate added is 0.3% by weight of the bentonite, and the amount of water added is 5 times the weight of the dry weight.

[0014] Specifically, the total amount of water added after dilution in step (2) is 15 times the total weight of bentonite, sodium carbonate and sodium hexametaphosphate, and centrifugation is performed at 3000 rpm for 3 minutes.

[0015] Specifically, in step (3), the solution is washed with water until the pH value is about 6.0 and the conductivity is below 1000 μS / cm.

[0016] Specifically, in step (6), water is used to prepare a slurry containing 5% purified montmorillonite, and lithium carbonate and oxalic acid are added at a molar ratio of 10% by weight of the purified montmorillonite, wherein the molar ratio of oxalic acid to lithium carbonate is 1.5 times. The high-pressure homogenizer is circulated twice at 70 Mpa, and the mixture is allowed to stand for 24 hours, dried, crushed and sieved, and the material under the sieve is taken to obtain lithiated montmorillonite.

[0017] Specifically, in step (7), the weight sum of 3-(4-ureaamino)propyltriethoxysilane and N,N'-dimethylthiourea is 4% of the lithium bentonite, wherein the weight ratio of 3-(4-ureaamino)propyltriethoxysilane to N,N'-dimethylthiourea is 7:1. In step (7), ethanol in an amount of 10% by weight of the lithium montmorillonite is added at the same time, sprayed on the surface of the lithium montmorillonite, ball milled for 30 minutes, and the material is poured out and dried for 10 minutes.

[0018] One of the objects of the present invention is to provide modified bentonite obtained by the above method.

[0019] One of the purposes of the present invention is to provide a cosmetic blush cream, comprising an aqueous phase component and an oil phase component. The aqueous phase component comprises, by weight, 2 to 5 parts of modified bentonite, 400 to 650 parts of vegetable glycerin, 20 to 40 parts of polyglycerol-10 myristate, 10 to 30 parts of polyglycerol-10 diisostearate, 50 to 70 parts of glycerol caprylate, 1 to 3 parts of 1,2-pentanediol, 1 to 2 parts of cinnamic acid, 10 to 20 parts of ceramide-3 and 5 to 15 parts of arginine. The oil phase component comprises, by weight, 20 to 40 parts of lycopene, 10 to 30 parts of safflower yellow, 20 to 40 parts of polyglycerol-3 triisostearate, 80 to 120 parts of caprylic triglyceride, 40 to 60 parts of jojoba oil, 40 to 60 parts of white meadowfoam seed oil, 8 to 12 parts of corn starch, 1 to 2 parts of lemon peel oil and 1 to 3 parts of vitamin C. The term "part(s)" is only used to indicate the relative proportion by weight of each component, and does not limit the absolute weight.

[0020] One of the purposes of the present invention is to provide a method for preparing the above-mentioned makeup blush cream, comprising:

[0021] (1) 20-40 parts of lycopene, 10-30 parts of safflower yellow, 20-40 parts of polyglycerol-3 triisostearate and 80-120 parts of caprylic triglyceride were mixed at a stirring speed of 400 rpm for 15 minutes to obtain a color paste;

[0022] (2) mixing the components in the water phase, adding them to an emulsifying device, heating them to 70° C., and stirring them at 40,000 rpm for 10 min to obtain a water phase mixture;

[0023] (3) mixing the color paste obtained in step (1), 40-60 parts of jojoba oil, 40-60 parts of meadowfoam seed oil and 8-12 parts of corn starch, and keeping the mixture at 70° C. to obtain an oil phase mixture;

[0024] (4) slowly adding the oil phase mixture in step (3) to the water phase mixture in the emulsification equipment in step (2), and homogenizing for 15 minutes at a rotation speed of 5000 rpm to obtain a homogenous mixture;

[0025] (5) The homogenous mixture obtained in step (4) is cooled to below 40° C., 1 to 2 parts of lemon peel oil and 1 to 3 parts of vitamin C are added, and the mixture is homogenized and mixed evenly. After standing for 10 minutes, the mixture is put into a mold to obtain a blush cream.

[0026] One of the purposes of the present invention is to provide the use of the modified bentonite prepared by the above method in the preparation of cosmetic blush cream.

[0027] Beneficial effects of the present invention:

[0028] The present invention obtains a raw material with significantly improved dispersibility, thickening performance and water absorption and swelling performance by inorganic and organic modification of bentonite. The modified bentonite can be applied to cosmetics to achieve thickening effects, and also has excellent air permeability, stable physical properties and excellent light stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 This is the XRD pattern of lithiated montmorillonite.

[0030] Figure 2 IR spectra of modified bentonite provided for Lithium-based montmorillonite (A), Group 3 (B), Group 2 (C), and Group 1 (D), respectively.

[0031] Figure 3 The aqueous viscosity curves of the modified bentonite provided for lithium-based montmorillonite, group 1, group 2 and group 3 respectively.

[0032] Figure 4 Viscosity curves of modified bentonite in alcohol system provided for lithium montmorillonite, group 1, group 2 and group 3 respectively.

[0033] Figure 5 2g expansion times of the modified bentonite provided for lithium montmorillonite, group 1, group 2 and group 3 respectively.

[0034] Figure 6 Stormer viscosity of lithium montmorillonite, modified bentonite provided in Group 1, Group 2 and Group 3 respectively in different solvents.

[0035] Figure 7 The moisture absorption / desorption rate curves of the cosmetic blush cream samples in the air provided for Group 1, Group 2, Group 3, Group 4 and Group 5 respectively.

[0036] Figure 8 The absorbance percentage of the cosmetic blush cream samples provided for Group 1, Group 2, Group 3, Group 4 and Group 5 under ultraviolet (UV) and sunlight conditions respectively. DETAILED DESCRIPTION

[0037] In order to make the purpose, technical scheme and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the examples. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. The reagents not described separately in detail in the present invention are all conventional reagents and can be obtained from commercial channels; the methods not described in detail are all conventional experimental methods and can be obtained from the prior art.

[0038] 1. Preparation of modified bentonite

[0039] 1. Purification and physicochemical properties of bentonite

[0040] The Liaoning bentonite ore was coarsely crushed to a particle size of less than 1 cm, and 2.5% sodium silicate and 0.3% sodium hexametaphosphate were added to the bentonite weight, and 5 times the weight of water was added to prepare a slurry, and the slurry was ball-milled in a fast grinder for 23 minutes to obtain a uniformly dispersed bentonite slurry. The slurry was diluted with water (the total amount of water added was 15 times the total weight of bentonite, sodium carbonate and sodium hexametaphosphate), centrifuged at 3000rpm for 3min, and the upper layer of concentrate slurry was taken. The obtained concentrate slurry was acidified to adjust the pH to 4.0-5.0 to remove carbonates and heavy metal removal reagents, etc., and the concentrate was centrifuged at 3000rpm for 3min to obtain the concentrate, which was washed with water to about pH=6.0 and the conductivity was below 1000 μS / cm to remove excess reagents, soluble ions and heavy metal ions. The washed slurry was centrifuged at 3500rpm for 5 minutes, the lower layer of paste was taken, and the concentrate was dried. The dried sample was crushed through a 200-mesh sieve to obtain purified montmorillonite.

[0041] Prepare a slurry containing 5% purified bentonite with water, add lithium carbonate and oxalic acid which are 10% by weight of the purified bentonite, wherein the molar ratio of oxalic acid to lithium carbonate is 1.5 times, cycle twice with a high-pressure homogenizer at 70 MPa, let stand and age for 24 hours, dry, crush and sieve, and take the material under the sieve to obtain lithiated montmorillonite.

[0042] XRD spectrum can reflect the phase composition, impurity type and content of the sample, as well as the type and interlayer spacing of montmorillonite, degree of crystallinity, etc. Shimadzu D / MAX-3B X-ray powder diffractometer, CuKα ray, graphite monochromator, tube voltage of 35kV, tube current of 30mA; scanning rate of 10° / min. Figure 1 As shown in the figure, after wet purification of Liaoning bentonite, the diffraction peaks in the XRD diagram are all characteristic peaks of montmorillonite, and basically no impurity diffraction peaks are observed, indicating that the montmorillonite content is high and contains few impurities after purification; the interlayer spacing of the sample is 12.5193A°, which belongs to the characteristic peak range of lithium-based montmorillonite.

[0043] 2. Bentonite modification

[0044] Group 1: The ball mill and the grinding ball medium were dried in advance, and lithium montmorillonite powder was added into the ball mill, 3-(4-urea amino)propyl triethoxysilane, N,N'-dimethylthiourea (D188700, Sigma), and the weight sum of 3-(4-urea amino)propyl triethoxysilane and N,N'-dimethylthiourea was 4% of lithium bentonite, wherein the weight ratio of 3-(4-urea amino)propyl triethoxysilane to N,N'-dimethylthiourea was 7:1. At the same time, ethanol at 10% of the weight of lithium montmorillonite was added and sprayed on the surface of lithium montmorillonite, and the ball mill was performed for 30 minutes. After the material was poured out, it was dried for about 10 minutes to evaporate the ethanol and a small amount of water vapor.

[0045] Group 2: The ball mill and the grinding ball medium were dried in advance, and lithium montmorillonite powder was added into the ball mill, and 3-(4-ureaamino)propyl triethoxysilane was 4% of lithium bentonite. At the same time, ethanol was added at 10% of the weight of lithium montmorillonite, and then sprayed on the surface of sodium montmorillonite. The ball mill was milled for 30 minutes, and the material was poured out and dried for about 10 minutes to evaporate the ethanol and a small amount of water vapor.

[0046] Group 3: The ball mill and the grinding ball medium were dried in advance, and lithium montmorillonite powder was added into the ball mill, and 3-aminopropyl triethoxysilane was 4% of lithium bentonite. At the same time, ethanol was added at 10% of the weight of lithium montmorillonite, and then sprayed on the surface of sodium montmorillonite. The ball mill was milled for 30 minutes, and the material was poured out and dried for about 10 minutes to evaporate the ethanol and a small amount of water vapor.

[0047] Nicolet 5DX Fourier transform infrared spectrometer, using KBr pellets for sample preparation, measuring wave number range: 400~4000cm -1 , resolution 4cm -1 .

[0048] Figure 2 This is the infrared spectrum comparison of bentonite before and after modification. As can be seen from the figure, the bentonite before and after modification has a 3621cm -1 、3438cm -1 、1633cm -1 and 1035 cm -1 Four characteristic absorption peaks, these are the characteristic absorption peaks in the bentonite structure. They are the OH stretching vibration of bentonite, the OH stretching vibration of interlayer water, the OH bending vibration of interlayer water and the Si-O-Si stretching vibration. The modified bentonite is at 2937 cm -1 The asymmetric stretching vibration of -CH2 appears at 1506cm -1 The peaks appearing at are the deformation vibration of -CH2 or the bending vibration of -NH2, which are the characteristic peaks of 3-(4-ureaamino)propyltriethoxysilane, indicating that 3-(4-ureaamino)propyltriethoxysilane has been successfully combined with the interlayer or surface of bentonite.

[0049] 3. Index analysis

[0050] (1) Viscosity

[0051] Viscosity is an important indicator of the thickening performance of reactive montmorillonite. According to the pharmacopoeia method and the operation process in actual production testing, the viscosity test method of the water system is as follows: The viscosity is closely related to the concentration. Taking 5% concentration as an example, add 475 mL of water to a 1 L beaker, and then weigh 25 g of sample. Under stirring conditions, slowly add the weighed sample to the water, continue stirring at 1500 rpm for 30 min to fully disperse the slurry, transfer it to the test cup, and test the viscosity with a rotational viscometer. Record the viscosity at 2min, 5min, 8min, 10min, 12min, 15min, 1h, 3h, 12h and 24h, and observe the thickening condition.

[0052] The viscosity test process in alcohol is as follows: appropriate water must be added to initiate the test, 15% water, 85% ethanol, to prepare a suspension of a certain concentration. First, weigh a certain amount of sample and add it to the water, stir to moisten it, let it stand for 5 minutes, add the remaining ethanol, and continue to stir at 1500rpm for 30 minutes. The subsequent operation process is the same as the viscosity test steps in water.

[0053] like Figure 3 and Figure 4 As shown, the 5-min and 24-h viscosities of the modified bentonites obtained in Group 1 and Group 2 in water and alcohol, respectively, are significantly higher than those of lithium montmorillonite and Group 3, indicating that the modification method and modified bentonite provided by the present invention are easier to increase their viscosity. Moreover, whether in a water system or an alcohol system, the viscosity of the modified bentonite provided by Group 1 basically reaches the maximum in about 10 minutes, while lithium montmorillonite and Group 3 need a longer time to reach the maximum viscosity, respectively, indicating that the modified bentonite provided by the present invention has a very high fractional property.

[0054] (2) Expansion force

[0055] Swelling power means 2g expansion times, which refers to the volume of 2g bentonite added to water in small amounts and multiple times, and is expressed in mL. It can intuitively reflect the water absorption and expansion performance of bentonite to a large extent. When the genus is the same, the higher the purity of montmorillonite, the greater the swelling power. Therefore, 2g expansion times can also be used as a technical indicator for distinguishing the content and genus of montmorillonite. The present invention tests and characterizes the swelling power of the sample according to the swelling power test method specified in the United States Pharmacopoeia USP 43-NF 38 bentonite standard. The specific test method is as follows: 100 mL of water is added to a stoppered measuring cylinder with a capacity of 100 mL, and 2 g of bentonite sample is added to the measuring cylinder in small amounts and multiple times. After the previous sample is wetted and falls from the water surface and settles, the next sample is added. The settled bentonite gradually absorbs water and expands at the bottom of the measuring cylinder. The suspended volume is recorded 2 hours after the sample is added.

[0056] like Figure 5As shown, the 2g expansion times of the modified bentonites obtained in Group 1 and Group 2 are significantly higher than those of lithium montmorillonite and Group 3, indicating that the modification method and modified bentonite provided by the present invention are easier to improve the water absorption and expansion performance.

[0057] (3) Stormer viscosity

[0058] Using the above-mentioned alcohol-water mixed system viscosity test method, each group of bentonite samples were placed in a mixture of different solvents and water with a volume ratio of 1:1 to test the Stormer viscosity. The solvents were ethanol, methanol, isopropanol, ethylene glycol, propylene glycol, ethylene glycol methyl ether, ethylene glycol ethyl ether and ethylene glycol butyl ether.

[0059] The Stormer viscometer is a test instrument mainly used to measure the viscosity of paints and other coatings. It can display the KU value or the load value (unit: g) associated with the KU value, which characterizes the viscosity of the sample being tested. It is suitable for measuring the viscosity of most non-Newtonian fluids, coatings, and paint-like liquids. Refer to the method of "Yang Xue; Stormer Viscometer Test Method; Journal Name: Hebei Chemical Industry; 2004 No. 2 2095-5979" to test the Stormer viscosity of the suspension (5min) after the viscosity is measured.

[0060] like Figure 6 As shown, the thickening performance of the modified bentonite obtained from Group 1 and Group 2 in different solvents is better than that of Group 1 and lithium montmorillonite.

[0061] 2. Application of the modified bentonite provided by the present invention as a cosmetic blush cream

[0062] 1. Preparation of blush cream

[0063] The modified bentonite provided by the present invention is used as a cosmetic blush cream to prepare a cosmetic blush cream. The details are as follows:

[0064] The aqueous phase ingredients include: 0.5 g of modified bentonite provided by groups 1 to 3, hectorite (group 4) or disteardimonium hectorite (group 5), 60 g of vegetable glycerin, 3 g of polyglyceryl-10 myristate, 2 g of polyglyceryl-10 diisostearate, 0.6 g of glyceryl caprylate, 0.2 g of 1,2-pentanediol, 0.1 g of cinnamic acid, 1.5 g of ceramide-3 and 1 g of arginine.

[0065] The oil phase ingredients include: 3g lycopene, 2g safflower yellow, 3g polyglyceryl-10 diisostearate, 10g caprylic acid triglyceride, 5g jojoba oil, 5g meadowfoam seed oil, 1g corn starch, 0.1g lemon peel oil and 0.2g vitamin C.

[0066] The preparation method of the makeup blush cream comprises:

[0067] (1) 3 g of lycopene, 2 g of safflower yellow, 3 g of polyglycerol-10 diisostearate and 10 g of caprylic acid triglyceride were mixed at a stirring speed of 400 rpm for 15 min to obtain a color paste;

[0068] (2) mixing the components in the water phase, adding them to an emulsifying device, heating them to 70° C., and stirring them at 40,000 rpm for 10 min to obtain a water phase mixture;

[0069] (3) mixing the color paste obtained in step (1), 5 g of jojoba oil, 5 g of meadowfoam seed oil and 1 g of corn starch, and keeping the mixture at 70° C. to obtain an oil phase mixture;

[0070] (4) slowly adding the oil phase mixture in step (3) to the water phase mixture in the emulsification equipment in step (2), and homogenizing for 15 minutes at a rotation speed of 5000 rpm to obtain a homogenous mixture;

[0071] (5) The homogenous mixture obtained in step (4) is cooled to below 40° C., 0.1 g of lemon peel oil and 0.2 g of vitamin C are added, and the mixture is homogenized and mixed evenly. After standing for 10 min, the mixture is put into a mold to obtain a blush cream.

[0072] 2. Air permeability test

[0073] Take fresh and clean hairless pig skin and apply the above-prepared blush cream with a sterile applicator stick at a coating amount of 1.5 mg / cm 2 , and then conduct air permeability test after natural drying for 20 minutes.

[0074] (1) Air permeability test

[0075] The absorption / release characteristics of water vapor in the air of the cosmetic blush cream samples prepared in groups 1 to 5 were measured under different temperature and humidity environments to evaluate the effect of the coating on the air permeability of the stone material. The constant humidity environment was created by a saturated salt solution.

[0076] Test process: Place the sample in a 65 ℃ drying oven and dry it to constant weight. Place it in a hygroscopic environment (temperature (30±1)℃, humidity 75%±2%) until constant weight, then switch to a dehumidifying environment (temperature (25±1)℃, humidity 30%±2%) until constant weight. Record the weight of the sample at each stage. The moisture absorption rate is 100%×(M1-M0) / M0, where M0 is the initial weight of the sample coated with the blush cream, and M1 is the constant weight after moisture absorption. The moisture release rate is 100%×(M2-M0) / M0, where M0 is the initial weight of the sample coated with the blush cream, and M2 is the constant weight after dehumidification.

[0077] like Figure 7As shown, the maximum moisture absorption / desorption rates of group 1 and group 2 are higher than those of other groups, and group 1 maintains a high moisture desorption rate for a longer time than that of other groups. This shows that the air permeability of the cosmetic blush cream sample prepared with modified bentonite as a raw material provided by the present invention is better than that of lithium montmorillonite or disteardimethylammonium hectorite.

[0078] (2) Physical stability of blush cream

[0079] According to the light industry standard QB / T 1857-2013, the following provisions are made for moisturizing creams: heat resistance (40±1℃) for 24 hours, the oil permeation rate is no more than 3% after returning to room temperature; cold resistance (-8±2℃) for 24 hours, and there is no obvious difference in properties after returning to room temperature. After heat resistance, cold resistance, centrifugation and freeze-thaw tests, it was found that the color blush cream prepared by the present invention did not have adverse phenomena such as stratification, melting and demulsification, and had good physical stability. Even under mechanical damage and harsh conditions, the appearance of the color blush cream still did not show obvious differences.

[0080] (3) Light stability test

[0081] The blush creams prepared in groups 1 to 5 were divided equally into 6 transparent sample bottles and irradiated continuously for 10 h at a distance of 5 cm from the UV lamp or for 2 h at noon for 5 days. During this period, a portion of the extract sample and the emulsion sample were taken out every 2 h for detection by UV-vis method, and the initial absorbance of the sample not treated with UV lamp was recorded at the same time.

[0082] Accurately weigh 1.5 g of the blush cream emulsion prepared by groups 1 to 5 treated with UV light and put it into a 25 mL beaker, add 10 mL of anhydrous ethanol and ultrasonicate for 15 min to fully dissolve it. Filter the emulsion with a needle equipped with a 0.45 μm filter membrane, and detect the filtrate with a UV spectrophotometer at 420 nm. Normalize the results (test absorbance / initial absorbance × 100%). With time as the horizontal axis and the normalized absorbance as the vertical axis, draw a photostability curve under UV irradiation conditions to compare the difference in absorbance trends between the solution and the emulsion.

[0083] like Figure 8As shown in the figure, the decrease in absorbance of each group of blush cream under sunlight conditions is not as large as that of ultraviolet radiation, indicating that ultraviolet radiation has a greater destructive effect on the blush cream. However, the absorbance of group 1 only decreases significantly under 1 hour of irradiation, and then it can maintain a stable absorbance. This shows that the blush cream made from the modified bentonite provided by the present invention is less affected by the irradiation of various light rays, and when applied to the skin, it has a stronger protective effect on the skin from the effects and damage of various light rays than other groups.

[0084] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily conceived by any technician familiar with the technical field within the technical scope disclosed by the present invention should be covered within the protection scope of the present invention.

Claims

1. A method for preparing modified bentonite, characterized in that: include: (1) preparing a slurry of crushed Liaoning bentonite ore particles with an aqueous solution containing sodium silicate and sodium hexametaphosphate, and grinding to obtain a dispersed bentonite slurry; (2) The bentonite slurry obtained in step (1) is diluted and centrifuged to obtain the concentrate slurry on the upper layer; (3) adding acid to the concentrate slurry obtained in step (2) to adjust the pH to 4.0-5.0, centrifuging to obtain the concentrate, and washing with water; (4) The washed slurry is centrifuged, the paste layer is taken out, and the concentrate is dried; (5) crushing and sieving the dried sample obtained in step (4) to obtain purified montmorillonite; (6) preparing a slurry of purified montmorillonite with water, mixing with lithium carbonate and oxalic acid, high-pressure homogenization, standing for aging, drying, and sieving to obtain lithiated montmorillonite; (7) The lithiated montmorillonite is mixed with 3-(4-ureaamino)propyltriethoxysilane and N,N'-dimethylthiourea, and then dried and ball-milled to obtain the modified bentonite.

2. The preparation method according to claim 1, characterized in that The particle size of the Liaoning bentonite ore particles in step (1) is less than 1 cm, the amount of sodium silicate added is 2.5% of the weight of the bentonite, the amount of sodium hexametaphosphate added is 0.3% of the weight of the bentonite, and the amount of water added is 5 times the weight of the dry weight.

3. The preparation method according to claim 1, characterized in that: The total amount of water added after dilution in step (2) is 15 times the total weight of bentonite, sodium carbonate and sodium hexametaphosphate, and centrifugation is performed at 3000 rpm for 3 minutes.

4. The preparation method according to claim 1, characterized in that In step (3), the sample is washed with water until the pH value is 6.0 and the conductivity is below 1000 μS / cm.

5. The preparation method according to claim 1, characterized in that In step (6), water is used to prepare a slurry containing 5% purified montmorillonite, and lithium carbonate and oxalic acid are added at a molar ratio of 10% by weight of the purified montmorillonite, wherein the molar ratio of oxalic acid to lithium carbonate is 1.5 times. The high-pressure homogenizer is circulated twice at 70 Mpa, and the mixture is allowed to stand for 24 hours, dried, crushed and sieved, and the material under the sieve is taken to obtain lithiated montmorillonite.

6. The preparation method according to claim 1, characterized in that In step (7), the sum of the weights of 3-(4-ureaamino)propyltriethoxysilane and N,N'-dimethylthiourea is 4% of the lithium bentonite, wherein the weight ratio of 3-(4-ureaamino)propyltriethoxysilane to N,N'-dimethylthiourea is 7:1; in step (7), ethanol in an amount of 10% by weight of the lithium montmorillonite is also added and sprayed on the surface of the lithium montmorillonite, ball milled for 30 minutes, and the material is poured out and dried for 10 minutes.

7. The modified bentonite obtained by the preparation method according to any one of claims 1 to 6.

8. A cosmetic blush cream, characterized in that: including water phase components and oil phase components; The aqueous phase component comprises, by weight, 2 to 5 parts of modified bentonite prepared by the preparation method of claim 1, 400 to 650 parts of vegetable glycerin, 20 to 40 parts of polyglycerol-10 myristate, 10 to 30 parts of polyglycerol-10 diisostearate, 50 to 70 parts of glyceryl caprylate, 1 to 3 parts of 1,2-pentanediol, 1 to 2 parts of cinnamic acid, 10 to 20 parts of ceramide-3 and 5 to 15 parts of arginine; The oil phase ingredients include, by weight, 20 to 40 parts of lycopene, 10 to 30 parts of safflower yellow, 20 to 40 parts of polyglycerol-3 triisostearate, 80 to 120 parts of caprylic triglyceride, 40 to 60 parts of jojoba oil, 40 to 60 parts of meadowfoam seed oil, 8 to 12 parts of corn starch, 1 to 2 parts of lemon peel oil and 1 to 3 parts of vitamin C.

9. The method for preparing the makeup blush cream according to claim 8, characterized in that: include: (1) 20-40 parts of lycopene, 10-30 parts of safflower yellow, 20-40 parts of polyglycerol-3 triisostearate and 80-120 parts of caprylic triglyceride were mixed at a stirring speed of 400 rpm for 15 minutes to obtain a color paste; (2) mixing the components in the water phase, adding them to an emulsifying device, heating them to 70° C., and stirring them at 40,000 rpm for 10 min to obtain a water phase mixture; (3) mixing the color paste obtained in step (1), 40-60 parts of jojoba oil, 40-60 parts of meadowfoam seed oil and 8-12 parts of corn starch, and keeping the mixture at 70° C. to obtain an oil phase mixture; (4) slowly adding the oil phase mixture in step (3) to the water phase mixture in the emulsification equipment in step (2), and homogenizing for 15 minutes at a rotation speed of 5000 rpm to obtain a homogenous mixture; (5) The homogenous mixture obtained in step (4) is cooled to below 40° C., 1 to 2 parts of lemon peel oil and 1 to 3 parts of vitamin C are added, and the mixture is homogenized and mixed evenly. After standing for 10 minutes, the mixture is put into a mold to obtain a blush cream.

10. Use of the modified bentonite obtained by the preparation method according to claim 1 in preparing a cosmetic blush cream.

Citation Information

Patent Citations

  • Organized clay, process for producing the same, and resin composite containing organized clay

    CN101711224A

  • Modified bentonite composite purifier and preparation method thereof

    CN103432993A